Treatment of high-solids synthetic domestic wastewater stream with high-rate anaerobic digesters - Aydınkaya, Zeynep. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2009., 2009)
Anaerobic treatment of domestic wastewater greatly reduces the organic load to water bodies with less energy input while generating renewable energy. This study focuses the performance of two different types of high-rate anaerobic digesters (anaerobic migrating blanket reactor [AMBR] and upflow anaerobic sludge blanket [UASB] reactor) treating domestic wastewater at 25°C. A 12 L AMBR and a 5 L UASB were fed with a synthetic colloidal wastewater simulating domestic wastewater at a chemical oxygen demand (COD) concentration of approximatelly 600 mg L-1 (this synthetic wastewater consisted of a solution of blended colloidal rice and dog food with trace elements and buffer). Both systems were operated at an identical hydraulic retention time (HRT) of 40 hours and operated for 195 days, however steady-state conditions were not achieved. Although the steaty-state conditions were not reached, data show that full-scale AMBR would be a good choice for domestic wastewater treatment.|Keywords: anaerobic, low strength, synthetic domestic wastewater, anaerobic migrating blanket reactor
Keywords: Sewage -- Purification -- Anaerobic treatment.; Sewage sludge digestion.; Anaerobic bacteria.